2011
DOI: 10.1007/s12195-011-0179-6
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Review of Mechanotransduction in Endothelial, Epithelial (Renal) and Dendritic Cells (Osteocytes)

Abstract: In this review we will examine from a biomechanical and ultrastructural viewpoint how the cytoskeletal specialization of three basic cell types, endothelial cells (ECs), epithelial cells (renal tubule) and dendritic cells (osteocytes), enables the mechano-sensing of fluid flow in both their native in vivo environment and in culture, and the downstream signaling that is initiated at the molecular level in response to fluid flow. These cellular responses will be discussed in terms of basic mysteries and paradoxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 177 publications
(300 reference statements)
1
58
0
Order By: Relevance
“…[21][22][23] These dendrites are important for mechanosensing (converting mechanical signals into intracellular bio chemical signals to osteoblasts and osteoclasts). 24 The loss of sensor-cell mechanosensitivity has been proposed as a cause of osteoporosis. 25 We hypothesize that PLS3 mutations lead to decreased mechanosensing of osteocytes, with subsequent dysregulation of bone modeling or remodeling, which results in osteoporosis and fractures.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] These dendrites are important for mechanosensing (converting mechanical signals into intracellular bio chemical signals to osteoblasts and osteoclasts). 24 The loss of sensor-cell mechanosensitivity has been proposed as a cause of osteoporosis. 25 We hypothesize that PLS3 mutations lead to decreased mechanosensing of osteocytes, with subsequent dysregulation of bone modeling or remodeling, which results in osteoporosis and fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Qazi et al [14] presented confocal images of HS for high metastatic kidney carcinoma cells (SN12L1) suspended in a 3D collagen I gel. The GCX thickness can be estimated from their Osteocytes are generally believed to be the mechanosensing cells in bone, and interstitial fluid flow shear stress induced by the cyclic compression of locomotion is widely believed to be the principal mechanical force applied to osteocytes, not the associated solid micro-strain [16]. Reilly et al [17], using the MLO-Y4 osteocytic cell line, demonstrated a GCX layer rich in HA.…”
Section: The Gcxmentioning
confidence: 99%
“…Especially, erythrocytes, or red blood cells, flow in blood capillaries interacting with the vascular endothelial surface layer. In general, it is believed that complex interactions occur between erythrocytes and the endothelial surface layer (ESL) (Weinbaum, et al, 2011). The ESL is also called endothelial glycocalyx layer (EGL), which consists of glycocalyx bushes, the height of which ranges from sub-micron order to a few-micron order (Gouverneur, et al, 2006).…”
Section: Introductionmentioning
confidence: 99%